The Effect of Artificial Intelligence (AI), Mobile Phones, and Teaching Models on Student Academic Achievement at SMAN 5 Palangka Raya - Tiurma Sari Dewi Flora Sinaga; Rinto Alexandro; Fendy Hariatama (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the influence of Artificial Intelligence (AI) utilization, mobile phone usage, and teacher learning models on student academic achievement in Economics at SMAN 5 Palangka Raya. Using a quantitative associative approach with a sample of 123 students, data were collected through valid and reliable questionnaires with a Cronbach’s Alpha of 0.887. The utilization of Artificial Intelligence (AI) in learning is closely associated with the use of mobile phones as the primary medium for students to access technology. Multiple linear regression analysis results show that the three variables simultaneously have a significant effect on academic achievement, contributing 98.9% (R2 = 0.989). Partially, AI (B= 0.434), mobile phones (B= 0.396), and teacher learning models (B = 0.499) have positive and significant effects with a significance of 0.000. The teacher learning model was found to be the most dominant factor. This suggests that the pedagogical strategies implemented by teachers play a central role in determining students' academic success. In conclusion, the integration of digital technology supported by adaptive pedagogical strategies is highly effective in enhancing students' academic performance in the digital era. While the integration of digital tools significantly boosts academic performance, pedagogical mastery remains the most critical factor in student success. The findings are expected to provide empirical evidence for schools and teachers in designing relevant and effective learning strategies in the digital era.